Antibodies to gp210 and understanding risk in patients with primary biliary cholangitis. (13th February 2021) - Haldar, Debashis; Janmohamed, Ashnila; Plant, Tim; Davidson, Matthew; Norman, Hannah; Russell, Emily; Serevina, Olivia; Chung, Kenneth; Qamar, Kashif; Gunson, Bridget; Hansen, Bettina; Richter, Alex; et al.
Abstract: Background and Aims: A variety of auto‐antibody assays are available as part of the clinical care of patients with liver disease. We sought to better understand the clinical utility of immune serological testing in patients with primary biliary cholangitis (PBC). Methods: We retrospectively analysed data from 2846 patients investigated for liver disease at a UK liver centre between 2001 and 2017. A total of 499 patients with PBC were identified. Immune serology results were examined for their diagnostic utility and prognostic significance to predict transplant‐free survival. Results: Antimitochondrial antibodies (AMAs) were specific (94.5%) and sensitive (85.6%) for PBC; antinuclear antibodies (ANAs) against glycoprotein 210 (gp210) and sp100 were specific (>98%) but not sensitive (<25%). The disease‐specific ANAs were detectable in 29.6% of AMA‐negative patients. Anti‐gp210 auto‐antibodies were significantly associated with elevated serum aminotransferase activity, bilirubin and liver stiffness at presentation ( P  < .010). Anti‐gp210 auto‐antibodies predicted non‐response to ursodeoxycholic acid (UDCA) by GLOBE criteria (39.3% vs 16.7%, P  = .005). Moreover, anti‐gp210 was independently associated with death or liver transplantation (HR 3.22, 95% CI 1.49‐6.96; P  = .003), after accounting for other significant baseline determinants of outcome. Serologic finding of anti‐gp210 antibodies conferred an independent risk of death or transplantation (HR 4.13, 95% CI 1.85‐9.22; P  = .001) after accounting for treatment response. Conclusion: In our single‐centre cohort of patients with PBC, the presence of anti‐gp210 was associated with an adverse presenting phenotype, predicted treatment non‐response and independently predicted reduced transplant‐free survival.